Investigating the effects of policy interest rate on the Thai economy in the FAVAR framework - Vajrapatkul, Adirek; Vajrapatkul, Pinmanee (Asian Journal of Economic Modelling, 2025)
The policy rate is a crucial monetary policy tool used by central banks to control economic conditions. Its main channel works via a transmission mechanism in which shocks to the policy rate proliferate through the financial system, which then affects the real economy. This study looks at how monetary policy affects the Thai economy and how it works by using a Factor-Augmented Vector Autoregressive (FAVAR) model, which can include both visible and hidden factors in the analysis, unlike traditional VAR methods. To achieve the objective of this study, monthly data from the Bank of Thailand database for the period between January 2011 and December 2023 were collected and analyzed using Principal Component Analysis, Vector Autoregressive technique, Granger causality tests, and impulse response analysis. The results indicate that interest rate hikes have temporary adverse effects on consumer confidence, retail sales, and asset prices. In addition, the findings show the interplay between interest rate shocks and labor markets, represented by worker outflow, employment levels, and job vacancies. The results also reflect the effective transmission of monetary policy through the money market channel, as market interest rates were aligned with the policy rate shock. These results suggest that monetary policy should be implemented in a balanced manner while considering the interconnections between various aspects of the economy. These results justify some supportive fiscal and labor market policies to promote consumption and reduce the adverse effects of monetary policy tightening.